PENYEDIAAN AIR BERSIH DI KOTA PEKANBARU (KAJIAN KASUS YAYASAN WAHA MITRA INDONESIA MEMENUHI KEPERLUAN MASYARAKAT) - Salindeho, Mercy G; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problem of save water on the big city is still have some interesting to be discuss allaround. Because save water is premiere needed for consumption of the society and have someinfluence on activity of that society's. So that in fulfillment of needs of save water for society weneed some role from our government and private company for distribution of that save waterfocus on edge of big city. Pekanbaru is city what have a PT. PDAM Tirta siak who have sometask to distribution save water to society in pekanbaru city. But they are not capable yet fordistribution save water to edge of Pekanbaru city.As for this phenomenally is PDAM Tirta Siak isn't make this easy for they needs with theycomplaint and this proved weakness of our government. There is still have private company tohelp the government that is Yayasan Waha Mitra Indonesia. This company beside distribution ofsave water, they make some education for important society got consumption of save water andhealthy in every day of life. The socialisation they make at Kecamatan Tenayan Raya.The method of this research is used method of quantities with descriptive approach.Technical of taking sample on this research is make some survey. Which is all of population usedfor sample are 22 samples.The result of this research prove the character of family who used the save water fromYayasan Waha Mitra Indonesia got their education in middle range of level, the religion on thisfamily more Islam than other. The number of member family have 4 - 6 peoples. Generally thefamily used save water from this Yayasan is majority of etnic malay cause their indigenous onthis area.Keywords: save water, socialization, response, society and service